FULFILLING THE RIGHTS OF TERRORISM VICTIMS ACCORDING TO POSITIVE LAW IN INDONESIA - Santi, Rovita Artha (Universitas Sultan Ageng Tirtayasa, 2023)
Acts of terrorism can occur anytime, anywhere, and affect anyone indiscriminately. The losses caused by acts of terrorism are very large, these acts are carried out by spreading widespread terror to the public, by threat or means of violence, whether organized or not. Terrorism can cause physical and/or psychological suffering for a long time, so terrorism is categorized as an extraordinary crime, one of which is the terrorist bombings in three churches in Surabaya. The terrorist attacks in Surabaya churches have caused many victims and these victims must be protected and have their rights fulfilled. With the revised terrorism law, attention to victim protection has increased, but the implementation of the law towards victims of terrorism is currently unknown. Through this background, the research to be studied is how the fulfillment of the rights of victims of terrorism and the mechanism for fulfilling the rights of victims of terrorism according to Law Number 5 of 2018 concerning Amendments to Law Number 15 of 2003 concerning Amendments to Government Regulation in Lieu of Law Number 1 of 2002 concerning Eradication of the Criminal Acts of Terrorism. This research uses normative juridical research methods with a statutory approach and case approach and uses secondary data sources and interviews, then the data is analyzed descriptively analytically. This research reaches the conclusion that the fulfillment of the rights of victims of terrorism has advanced after the revision of the law, which consists of medical assistance, psychosocial and psychological rehabilitation, compensation for families in the event of death, compensation and restitution which are quite complete compared to the previous law, besides that the law also applies retroactively to victims of terrorism before the law was passed. Furthermore, the mechanism of fulfilling the rights of victims of terrorism in this law has changed in that victims can apply for their rights without going through a court decision, namely with a victim's certificate from the National Counterterrorism Agency.